Epistemology of Language as a Logical Instrument in Economics - Syafiqoh Mubarokah; Akhmad Afandi (Journal of Community Service and Rural Development, 2025)
The study of language through the lens of epistemology offers a foundational framework for understanding logic in economic reasoning. This paper explores how linguistic structures and meaning contribute to the formation of rational economic thought, particularly in decision-making, policy discourse, and market behavior. By examining the philosophical roots of language—its definitions, use, and interpretation—we gain insight into how economic agents construct and communicate knowledge. The interplay between semantics and logic serves not only as a tool for clarity and coherence but also as a mechanism that shapes economic narratives and ideologies. This interdisciplinary approach bridges philosophical inquiry and economic theory, revealing how language functions as both a medium and a method of rational economic analysis.